Isolation of high-quality total RNA from leaves of myrciaria dubia Camu camu - Castro Gómez, Juan Carlos; Egoavil Reátegui, Alina del Carmen; Torres Flores, Julián; Ramírez Saavedra, Roberson; Imán Correa, Sixto Alfredo (Taylor & Francis, 2017)
Myrciaria dubia is a main source of vitamin C for people in the Amazon region. Molecular studies of M. dubia require high-quality total RNA from different tissues. So far, no protocols have been reported for total RNA isolation from leaves of this species. The objective of this research was to develop protocols for extracting high-quality total RNA from leaves of M. dubia. Total RNA was purified following two modified protocols developed for leaves of other species (by Zeng and Yang, and by Reid et al.) and one modified protocol developed for fruits of the studied species (by Silva). Quantity and quality of purified total RNA were assessed by spectrophotometric and electrophoretic analysis. Additionally, quality of total RNA was evaluated with reverse-transcription polymerase chain reaction (RT-PCR). With these three modified protocols we were able to isolate high-quality RNA (A260nm/A280nm >1.9 and A260nm/A230nm >2.0). Highest yield was produced with the Zeng and Yang modified protocol (384+/-46microg ARN/g fresh weight). Furthermore, electrophoretic analysis showed the integrity of isolated RNA and the absence of DNA. Another proof of the high quality of our purified RNA was the successful cDNA synthesis and amplification of a segment of the M. dubia actin 1 gene. We report three modified protocols for isolation total RNA from leaves of M. dubia. The modified protocols are easy, rapid, low in cost, and effective for high-quality and quantity total RNA isolation suitable for cDNA synthesis and polymerase chain reaction.